2013
DOI: 10.3126/njst.v13i2.7733
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physicochemical and Microbiological Parameters of Drinking Water Supplied from Distribution Systems of Kathmandu Municipality

Abstract: Microbial pathogens in drinking water are primary cause in gastrointestinal and waterborne diarrheal diseases. Public health authorities still have not achieved success in controlling the most common waterborne diseases in Nepal. The objective of this study was to assess the quality of drinking water supplied from distribution system of Kathmandu. A total of 114 water samples were collected from 4 distribution stations. The physicochemical and microbiological analyses of water were conducted. Heterotrophic pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The study was similar to previous studies where 100% of groundwater was contaminated by coliform (Diwakar et al 2008), 97.37 % of tube well (Bajracharya et al 2007) and 94.7 % of well water (Prasai et al, 2007). Previous studies evaluating different water sources such as processed water, tap water and treated water revealed that the samples were highly contaminated by total coliform bacteria (Maskey et al 2020, Maharjan et al 2018, Bishankha et al 2012, Shakya et al 2012.The result was also justified by the previous result where almost all waters of shallow wells were not suitable for drinking because of the presence of E. coli and only 29% of deep tube wells had drinkable waters (Sakamoto et al, 2012). The detection of coliform bacteria is directly related to public health concerns and it should be monitored for the microbial quality of ground water.…”
supporting
confidence: 90%
“…The study was similar to previous studies where 100% of groundwater was contaminated by coliform (Diwakar et al 2008), 97.37 % of tube well (Bajracharya et al 2007) and 94.7 % of well water (Prasai et al, 2007). Previous studies evaluating different water sources such as processed water, tap water and treated water revealed that the samples were highly contaminated by total coliform bacteria (Maskey et al 2020, Maharjan et al 2018, Bishankha et al 2012, Shakya et al 2012.The result was also justified by the previous result where almost all waters of shallow wells were not suitable for drinking because of the presence of E. coli and only 29% of deep tube wells had drinkable waters (Sakamoto et al, 2012). The detection of coliform bacteria is directly related to public health concerns and it should be monitored for the microbial quality of ground water.…”
supporting
confidence: 90%
“…Enteric bacteria are found in biofi lm in drinking water distribution system of Kathmandu valley (Shakya et al 2012 (Shrestha et al 2016;Shrestha et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Safe drinkable water is highly linked with the health status and wellbeing of humans (WHO, 1997;Sharma, et al, 2005). Several studies conducted in the past at different parts of Nepal reported the substandard quality of drinking water due to exceedance of physical, chemical and biological agents above safe limits (Warner, et al, 2008;Pandey & Shakya, 2011;Shakya, et al, 2012;Aryal, et al, 2012;Koju, et al, 2014). More than 10,000 children under 5 years old lose their lives annually by consuming contaminated drinking water (WaterAid, 2011).…”
Section: Introductionmentioning
confidence: 99%